O livro das mil e uma noites em Vozes do deserto, de Nélida Piñon - Gerlach, Ana Paula Xavier (2020)
The present work aims at analyzing the main elements of Nélida Piñon's Vozes do deserto, a reinterpretation of the one thousand and one nights, using as reference for comparison the manuscripts translated by Mamede Mustafa Jarouche, published in three volumes, titled Livro das mil e uma noites. For the analysis of the heroine constructed in both works, we used the theory presented by Joseph Campbell in The Hero with a Thousand Faces, analyzing the construction of Scherezade equally in both works, highlighting the same characteristics that indicate her role as the heroine in the most recent work. In addition to the analysis of the construction of the myth, we also analyzed the structure of the narratives, the representation of the works in their time, and how the characters were approached, emphasizing their particularities to each work. To conclude the work, we readdress the data collected, analyzing similarities, differences and innovations in Piñon’s most recently published work, highlighting the main elements that indicate the contemporary reinterpretation.